Implementation of a Legionella Ordinance for Multifamily Housing, Garland, Texas. Issue 6 (November 2017) - Whitney, Ellen A.; Blake, Sarah; Berkelman, Ruth L.
Abstract : Context: The incidence of legionellosis has sharply increased in the United States as a result of contaminated water systems. Jurisdictions across the country are considering whether to develop and implement regulations to protect individuals against Legionnaires' disease with its associated high morbidity and mortality. Objective: This article sheds light on the implementation and effectiveness of a 2005 citywide Legionella testing mandate of multifamily housing cooling towers in Garland, Texas. This ordinance has been in place for more than 10 years and represents the first of its kind in the United States to mandate routine testing of cooling towers for Legionella in multifamily housing. Design, Setting, and Population: We utilized a mix of both qualitative and quantitative methods to explore the development, adoption, and implementation of the ordinance. Phone interviews were conducted with individuals from the City of Garland Health Department and apartment managers. Quantitative data included public health surveillance data on legionellosis. Main Outcome Measures: Barriers and facilitators of implementation, number and percentage of cooling towers from multifamily housing units that tested positive for Legionella by year, and number of legionellosis cases by year in Garland, Texas. Results: Study outcomes highlight key themes that facilitated the successful implementation of the Legionella testing mandate, including the importance of timing, leadership support, stakeholder engagement, and education and outreach. The number of contaminated cooling towers was reduced over time. Conclusion: Mandatory monitoring for legionella in a local jurisdiction may result in reduced risk of legionellosis from cooling towers through raising awareness and education of building owners and managers about the need to prevent, detect, and remediate legionella contamination in their building water systems. Garland, Texas, broke new ground in the United States in moving toward primary prevention of legionellosis. The ordinance may be useful both in serving to educate and increase awareness about the need for Legionella prevention and to monitor effectiveness of maintenance procedures.